(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Contemporary border control and migration management policies and practices national wide and within the European Union are usually structured within a framework characterised by a collaboration between public and private interests. Migration is often related to various risks to national security, including some of them closely related to the regulatory framework. Migration itself, as a complex issue requires the provision of international protection, especially as the pressure to EU external borders provide challenges to border EU countries member states. This article focuses on specific regulations introduced within the new European union Pact on Migration and Asylum refer to migration management regulation, as its implementation requires exceed of capacities of EU member states countries as well as introduction of specific mechanisms for strengthening cooperation and solidarity in fight against negative consequences for illegal migration.